Alcohol: a missed opportunity. A survey of all accident and emergency departments in England. Issue 8 (25th July 2007) - Patton, R; Strang, J; Birtles, C; Crawford, M J
Abstract : Aim: To determine the extent to which the recommendations of the alcohol harm reduction strategy for England and the Choosing Health white paper for the provision of screening and brief interventions for hazardous and harmful drinkers have been adopted by accident and emergency departments. Method: Telephone/postal survey of all 191 Type 1 departments in England. The survey was part of a larger study investigating the impact of the changes in the licensing act (2004) on alcohol-related attendances. Results: 4 departments use formal screening tools and 24 ask general questions about consumption (98.9% response rate). Blood alcohol levels were measured as required by 100 departments. No departments routinely measure blood alcohol, and 84 departments never assess blood alcohol levels. Alcohol-related attendances were formally recorded by 131 departments. Access to an alcohol health worker or a clinical nurse specialist was reported by 32 departments. Discussion: Although departments may be willing to address hazardous alcohol consumption, the low numbers of departments utilising formal screening tools suggests that patients who may benefit from help or advice remain undetected.